Signal Strength based Self Reconfiguration to Ensure Reliability in Wireless Sensor Networks - M.A. Manivasagam; T.V Ananthan (Institute of Advanced Engineering and Science, 2018)
Providing reliability in Wireless sensor networks is considered to be a challenging task, due to the limited capabilities in terms of energy, power and memory. The applications of these systems run in sensors with low level programming abstractions, limited capabilities and routing protocols. In this paper, we propose a strategy to adjust radios in the sensor network depending on the signal strength of the neighboring nodes to ensure reliability using self reconfiguration (S2R2). Redundancy-based reliability is achieved by performing encoding/decoding either at the source and the destination node or each pair of communicating sensor nodes from the source to the destination. Along with the reliability, the link and the stability of the link are checked. The stability of the route makes the route a valid one to send data. Simulation analysis shows that the proposed mechanism performs better in terms of stability and reliability compared to the existing mechanism